La Dichiarazione Universale dei Diritti dell’Uomo a settant’anni dalla approvazione.: Ricerca esplorativa sulla conoscenza e opinione degli studenti sui diritti umani (Società e diritti, 2020)
The author illustrates the results of a KOL (Knowledge and Opinion about Law) exploratory research on the conception of human rights of Italian and foreign university students enrolled in the University of Milan. The "long" list of human rights present in the Universal Declaration is considered by most of the interviewees to be an indispensable part of the legal culture in Italy and acts as a "driver of change" oriented towards justice.